Serotonin syndrome triggered by a single dose of suboxone - Isenberg, Derek; Wong, Stella C.; Curtis, John A. (The American journal of emergency medicine, 2008)
Suboxone (buprenorphine/naloxone) is an oral medication used for the treatment of opiate dependence. Because of its mixed properties at the opiate receptors, buprenorphine has a ceiling on its euphoric effects. We report the first case of serotonin syndrome caused by buprenorphine and review other medications implicated in serotonin syndrome. A 54-year-old man on tricyclic antidepressants took an unprescribed dose of buprenorphine/naloxone. He presented to the emergency department with signs and symptoms of severe serotonin syndrome including clonus, agitation, and altered mental status. His agitation was not controlled with benzodiazepines and was electively intubated. At the recommendation of the toxicology service, cyproheptadine, a serotonin receptor antagonist, was administered with improvement in the patient's symptoms. Emergency physicians should be aware of the potential of buprenorphine/naloxone to trigger serotonin syndrome.